Effects of exercise on obesity-induced mitochondrial dysfunction in skeletal muscle - Heo, Jun-Won; No, Mi-Hyun; Park, Dong-Ho; Kang, Ju-Hee; Seo, Dae Yun; Han, Jin; Neufer, P. Darrell; Kwak, Hyo-Bum (My University, 2017)
Obesity is known to induce inhibition of glucose uptake, reduction of lipid metabolism, and progressive loss of skeletal muscle function, which are all as- sociated with mitochondrial dysfunction in skeletal muscle. Mitochondria are dy- namic organelles that regulate cellular metabolism and bioenergetics, including ATP production via oxidative phosphorylation. Due to these critical roles of mitochon- dria, mitochondrial dysfunction results in various diseases such as obesity and type 2 diabetes. Obesity is associated with impairment of mitochondrial function (e.g., decrease in O2 respiration and increase in oxidative stress) in skeletal muscle. The bal- ance between mitochondrial fusion and fission is critical to maintain mitochondrial homeostasis in skeletal muscle. Obesity impairs mitochondrial dynamics, leading to an unbalance between fusion and fission by favorably shifting fission or reducing fusion proteins. Mitophagy is the catabolic process of damaged or unnecessary mito- chondria. Obesity reduces mitochondrial biogenesis in skeletal muscle and increases accumulation of dysfunctional cellular organelles, suggesting that mitophagy does not work properly in obesity. Mitochondrial dysfunction and oxidative stress are reported to trigger apoptosis, and mitochondrial apoptosis is induced by obesity in skeletal muscle. It is well known that exercise is the most effective intervention to protect against obesity. Although the cellular and molecular mechanisms by which exercise protects against obesity-induced mitochondrial dysfunction in skeletal mus- cle are not clearly elucidated, exercise training attenuates mitochondrial dysfunction, allows mitochondria to maintain the balance between mitochondrial dynamics and mitophagy, and reduces apoptotic signaling in obese skeletal muscle.